2010
DOI: 10.1371/journal.pone.0015268
|View full text |Cite
|
Sign up to set email alerts
|

Affective Response to a Loved One's Pain: Insula Activity as a Function of Individual Differences

Abstract: Individual variability in emotion processing may be associated with genetic variation as well as with psychological predispositions such as dispositional affect styles. Our previous fMRI study demonstrated that amygdala reactivity was independently predicted by affective-cognitive styles (phobic prone or eating disorders prone) and genotype of the serotonin transporter in a discrimination task of fearful facial expressions. Since the insula is associated with the subjective evaluation of bodily states and is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 83 publications
1
34
0
1
Order By: Relevance
“…Indeed, individuals presenting these psychological predispositions tend to be more viscerally aware, more sensitive in the detection of changes in bodily states occurring during emotions and feelings. We showed this in a recent fMRI study, where such an individual variability in emotion processing was demonstrated (Mazzola et al, 2010).…”
Section: Sadness: Between Normality and Psychopathologymentioning
confidence: 56%
“…Indeed, individuals presenting these psychological predispositions tend to be more viscerally aware, more sensitive in the detection of changes in bodily states occurring during emotions and feelings. We showed this in a recent fMRI study, where such an individual variability in emotion processing was demonstrated (Mazzola et al, 2010).…”
Section: Sadness: Between Normality and Psychopathologymentioning
confidence: 56%
“…19,21,22 On a related note, in the sedentary-landscape contrast condition, O-W women showed comparatively weaker activation in the left posterior insula (BA 13), another area implicated in the anticipation and experience of negative affect, 46,47 fear and pain processing. 48,49 Although at odds with our hypothesis that the O-W might show stronger reward activation during exposure to sedentary images, decreased responsiveness in this area, compared with leaner controls, during exposure to sedentary images might have reflected comparatively more negative reinforcement (that is, reductions in aversive affective experiences) in the O-W group. From this perspective, behavioral evidence of preferences for sedentary activity or alternatives to physical activity 15,16 and increased time spent in sedentary activities among the O-W/obese can be reframed as a partial reflection of reductions in negative emotional reactions to increased physical activity rather than purely as a result of increased reward value such activities might engender.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, insula patients had significantly lower scores in the AE scale as well as EC subscale. In the behavioral paradigms research, furthermore, the insula is a key structure in the perception of oneself and others' pain (Engen & Singer, 2013;Mazzola et al, 2010). Multiple imaging studies have shown that sharing pain in others most strongly activated the insular cortex (particularly the AI) (Lamm et al, 2011;Sheng, Liu, Li, Fang, & Han, 2014).…”
Section: Evaluation Of Aementioning
confidence: 99%